Economic Dispatch with Transmission Losses in a Distributed Generation Network of Bahawalpur - Khan Ahmad; Rashid Zeeshan; Umer Farhana; Yousaf Abdur Rehman; Saeed Arif (Electrical, Control and Communication Engineering)
In an electrical power system, the ultimate aim is to generate and deliver electrical energy to consumer side with minimum cost involved. Thus, least fuel cost, effective unit commitment and minimum transmission losses are desirous to achieve economic dispatch in a distributed generation network. In this research, economic dispatch considering transmission losses in a distributed generation network of Bahawalpur is reported. A MATLAB algorithm is designed which gives optimum division of power between two power plants and their transmission losses. Power plants considered here are thermal power plant Muzafargarh and Kot Addu Power Company (KAPCO), the former being located at smaller distance from Bahawalpur district. Finally, load trend of Bahawalpur district, optimum generation verses power demand, associated transmission losses, penalty factor and fuel cost economy are shown in the Results Section through graphs and tables. It is concluded that thermal power plant shares higher contribution of load power due to smaller distance from load and, thus, smaller transmission losses ensuring minimum cost operation.